Evolution of temporomandibular joint reconstruction: from autologous tissue transplantation to alloplastic joint replacement - Hanghang Liu; Liwei Huang; Shibo Liu; Linyi Liu; Bolun Li; Zizhuo Zheng; Yao Liu; Xian Liu; En Luo (International Journal of Oral Science)
Abstract The reconstruction of the temporomandibular joint presents a multifaceted clinical challenge in the realm of head and neck surgery, underscored by its relatively infrequent occurrence and the lack of comprehensive clinical guidelines. This review aims to elucidate the available approaches for TMJ reconstruction, with a particular emphasis on recent groundbreaking advancements. The current spectrum of TMJ reconstruction integrates diverse surgical techniques, such as costochondral grafting, coronoid process grafting, revascularized fibula transfer, transport distraction osteogenesis, and alloplastic TMJ replacement. Despite the available options, a singular, universally accepted ‘gold standard’ for reconstructive techniques or materials remains elusive in this field. Our review comprehensively summarizes the current available methods of TMJ reconstruction, focusing on both autologous and alloplastic prostheses. It delves into the differences of each surgical technique and outlines the implications of recent technological advances, such as 3D printing, which hold the promise of enhancing surgical precision and patient outcomes. This evolutionary progress aims not only to improve the immediate results of reconstruction but also to ensure the long-term health and functionality of the TMJ, thereby improving the quality of life for patients with end-stage TMJ disorders.